2017
DOI: 10.3758/s13414-017-1381-y
|View full text |Cite
|
Sign up to set email alerts
|

Object-substitution masking weakens but does not eliminate shape interactions

Abstract: At any moment, some objects in the environment are seen clearly, whereas others go unnoticed. Whether or not these gaps in awareness are actually problematic may depend on the extent that information about unseen objects is lost. Determining when and how visual awareness and visual processing become linked is thus of great importance. Previous research using object-substitution masking (OSM) demonstrated that relatively simple visual features, such as size or orientation, are still processed even when they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 73 publications
2
6
0
Order By: Relevance
“…This is a perceptual consequence of segmentation—objects are perceived to be more distinct than they really are. Similar distortions have been observed for perception of size (Fortenbaugh, Sugarman, Robertson, & Esterman, 2019), shape (Sweeny, D’Abreu, Elias, & Padama, 2017), spatial location (Badcock & Westheimer, 1985; DiGiacomo & Pratt, 2012; Suzuki & Cavanagh, 1997), and direction of motion (Thornton, 2002). Segmentation is likely involved in distinguishing figure (i.e., object) from ground (i.e., background; Grossberg, 1994; Westheimer & Levi, 1987) and can even act at during decision-making (Fritsche & de Lange, 2019; Zamboni, Ledgeway, McGraw, & Schluppeck, 2016).…”
supporting
confidence: 72%
“…This is a perceptual consequence of segmentation—objects are perceived to be more distinct than they really are. Similar distortions have been observed for perception of size (Fortenbaugh, Sugarman, Robertson, & Esterman, 2019), shape (Sweeny, D’Abreu, Elias, & Padama, 2017), spatial location (Badcock & Westheimer, 1985; DiGiacomo & Pratt, 2012; Suzuki & Cavanagh, 1997), and direction of motion (Thornton, 2002). Segmentation is likely involved in distinguishing figure (i.e., object) from ground (i.e., background; Grossberg, 1994; Westheimer & Levi, 1987) and can even act at during decision-making (Fritsche & de Lange, 2019; Zamboni, Ledgeway, McGraw, & Schluppeck, 2016).…”
supporting
confidence: 72%
“…We found no evidence that the integration of global organizations into ensemble representations depended on whether those global organizations were masked. This is consistent with recent findings that information about global form can be processed even when it is suppressed from awareness (Chung & Khuu, 2014;Mudrik et al, 2011), as well as our previous work in which we found that global organization biased perception of individual shapes, even when they were masked out of awareness (Sweeny et al, 2017). Ensemble representations have been shown to sometimes include visual information about which a perceiver is unaware (Fischer & Whitney, 2011;Parkes et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…This may seem like a surprising prediction, but in fact we found in a previous investigation that global organizations only distorted perception of individual shapes when those shapes had tall aspect ratios (Sweeny, Grabowecky, & Suzuki, 2011b). Finally, in our previous work we found that global organizations biased perception of individual shapes even when they were not visible (Sweeny et al, 2017). We thus predicted that, here, global aspect ratio would still bias perception of a set's average shape in the masked condition, but potentially with reduced strength compared to the unmasked condition.…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations